KEPENTINGAN INDONESIA MENGIMPOR GULA DARI BRAZIL TAHUN 2015 -2017 - Novrianto Sitorus; Afrizal " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2020)
Indonesia has a deficit in sugar production, the production of sugar produced by sugar factories in Indonesia has been largely inoperative, many factories are old and the technology used is behind, so many factories have been closed, this is the cause of Indonesia experiencing a sugar production deficit.          The research method used is descriptive analytic method. The perspective used in research is the perspective of liberalism, the perspective of liberalism is the perspective that views that humans basically have a good nature, humans still have a conscience to create a peace. The theory used in this research is import policy theory, import is the activity of entering goods into customs areas. Companies or individuals who carry out these import activities are called importers.          The high demand for sugar, the Indonesian government adopted a policy of importing sugar from Brazil, Brazil is the largest sugar producing country in the world, the sugar produced by Brazil is of high quality for Indonesian people to consume and sugar is very cheap compared to sugar producing countries. Based on the results of the analysis of the discussion it can be concluded that the results of Indonesia's imported sugar trade conditions have fluctuated within a few years, not always experiencing an increase in the number of products, this is due to the amount of Indonesian sugar production experiencing a deficit, the price of sugar produced by local sugar products is very high while consumption Indonesian sugar has increased every year. Sugar Imports to meet the existing Sugar Production Deficit in Indonesia, Brazilian Sugar Production can be consumed by Indonesians and sugar prices in Brazil are very cheap. From some of these things the Government of Indonesia adopted a policy to import sugar from Brazil. Keywords : Indonesian government, Production, Brazil,  Sugar,  Factories,                   Import policy theory,  Liberalism Perspective.